The identity crisis of the European Union’s Corporate Law. A review on the Polbud case and derivated matters - González López, José Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The regulation of life and death of companies is a competence of each EU member states. Due to a lack of interest in harmonizing, the CJEU has been in charge of solving the conflict between the freedom of establishment and the mentioned lack of interest. This paper contains a critical commentary of the case law of the CJEU and the problems that it shows. Such problems are basically the contradictions between the lax and strict corporate regulations of the different Member States and, also, the great contradiction: the two opposed theories for the regulation of the lex societatis that coexist in European territory.
Keywords: registered office; transfer; real seat; incorporation; enterprise; company